2008
DOI: 10.1017/s1481803500010125
|View full text |Cite
|
Sign up to set email alerts
|

Rural emergency department use by CTAS IV and V patients

Abstract: Objective: For a variety of reasons, many emergency department (ED) visits are classified as less-or nonurgent (Canadian Triage and Acuity Scale [CTAS] level IV and V). A recent survey in a tertiary care ED identified some of these reasons. The purpose of our study was to determine if these same reasons applied to patients presenting with problems triaged at a similar level at a lowvolume rural ED. Methods: A 9-question survey tool was administered to 141 CTAS level IV and V patients who attended the South Hu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
28
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 21 publications
1
28
0
Order By: Relevance
“…We hypothesized that in Ontario, where a shortage of primary care physicians is recognized across the province, less urgent presentations to the ED could be a reflection of immediate access barriers to alternative sites of care such as family doctors or walk‐in clinics 14,24,25 . This hypothesis is supported by single‐site surveys from Canada that have demonstrated that while less urgent ED use is not associated with lack of a family doctor, it is associated with an inability to access timely primary care 26,27 . A Canadian population‐based study demonstrated that recent primary care reform efforts in Ontario have led to increased rostering of individuals of higher SES than expected for the population, also suggesting reduced primary care access for those with lower SES 28 .…”
Section: Discussionmentioning
confidence: 92%
“…We hypothesized that in Ontario, where a shortage of primary care physicians is recognized across the province, less urgent presentations to the ED could be a reflection of immediate access barriers to alternative sites of care such as family doctors or walk‐in clinics 14,24,25 . This hypothesis is supported by single‐site surveys from Canada that have demonstrated that while less urgent ED use is not associated with lack of a family doctor, it is associated with an inability to access timely primary care 26,27 . A Canadian population‐based study demonstrated that recent primary care reform efforts in Ontario have led to increased rostering of individuals of higher SES than expected for the population, also suggesting reduced primary care access for those with lower SES 28 .…”
Section: Discussionmentioning
confidence: 92%
“…Several studies investigating nonurgent patients' reasons for ED visits underscore other reasons for seeking ED care [10,11,19]. These studies found that it was common for nonurgent patients to seek ED care because they believed they were suffering from a serious condition or that they were worried about their symptoms or they were referred to the ED.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have analysed this phenomenon and investigated what events bring patients to the ED. These suggestions have, however, not been supported by a number of studies [5,[10][11][12]. These suggestions have, however, not been supported by a number of studies [5,[10][11][12].…”
Section: Introductionmentioning
confidence: 88%
See 2 more Smart Citations